INTEGRATING LEARNING STYLES AND MULTIPLE INTELLIGENCES WITHIN THE 5E LEARNING CYCLE TO IMPROVE STUDENTS’ HIGHER-ORDER THINKING IN CHEMISTRY - Febi Dwi Widayanti; Eko Yuniarto; Nurin Fitriana; Endang Prihatiningsih (JCER (Journal of Chemistry Education Research), 2026)
This study aims to analyze the effects of grouping strategies based on students’ learning styles and levels of Multiple Intelligences (MI) on their Higher-Order Thinking Skills (HOTS) in chemistry learning within the 5E Learning Cycle model. A 2×3 factorial experimental design was employed, involving senior high school students in East Java who were categorized according to learning style (homogeneous or heterogeneous groups) and MI levels (high, moderate, or low). Research instruments included an MI questionnaire, a HOTS test developed from the revised Bloom’s taxonomy indicators, and observation sheets for learning activities. Data were analyzed using two-way ANOVA and interaction tests. The findings revealed that both grouping strategies and MI levels had a significant effect on students’ HOTS, with a meaningful interaction between the two factors. Students with higher MI levels who participated in homogeneous learning-style groups demonstrated the greatest improvement in HOTS, particularly in the analyzing and creating dimensions. Integrating learning styles and MI within the 5E model was proven to enhance the effectiveness of each learning phase by activating exploratory and reflective cognitive processes. Theoretically, this study extends the 5E model into a Differentiated Learning Cycle (DLC)—an adaptive constructivist approach that integrates students’ learning profiles into the chemistry learning process. The findings contribute empirically to the development of differentiated instructional strategies aimed at enhancing students’ HOTS and twenty-first-century scientific literacy.